Finding Dory the essential guide - Dakin, Glenn (New York, New York DK Publishing, 2016)
A fan's guide to the sequel to Finding Nemo blends movie stills and character art with profiles of old and new characters as well as information on key locations, themes, and iconic moments, while providing facts about life in the ocean
At head of title: Disney Pixar
Comic strips
1
Keywords: Finding Dory (Motion picture) -- Juvenile literature; Finding Dory (Motion picture); Marine animals -- Juvenile literature; Marine animals; Picture stories